Dnevna mobilnost v Sloveniji - Bole, David (Georitem, 2009)
The main goal of the entire project was so to investigate problems of daily commuting of workers, pupils and students, especially from the modal split point of view. The project is structured in two parts.The first part of the book is an extensive analysis of modal split by different relations (routes) and groups of commuters (pupils, secondary school pupils, students and workers). We tried to establish the areas in Slovenia where the usage of public transport is the weakest and to provide credible causes of that. The data of modal split was compared with the supply of public transport and with this we established that there is a significant link between the high public transportation usage and the high quality and competitiveness offer of public transportation vis-à-vis personal transportation.The next chapter was dedicated to particular pilot areas where the supply of public transport was greatly improved (Dol pri Ljubljani, Ankaran, Idrija, Nova Gorica). With the method of field interviewing and passenger counting we found out that the greatly improved offer of public transport does not necessarily cause a greater demand for public transport and thus the shift towards a more sustainable mobility.The synthesis of the book is in ten recommendations of possible transport policy measures for the purpose of achieving more sustainable mobility patterns with workers and students.